渐趋于零 ：新加坡末代华校群体初探 = Getting to null : a preliminary survey on Singapore’s last Chinese-educated generation - 汪来昇 Ang, Lai Sheng (2014)
在教育政策、社会转型骤变与交汇的1980年代里，华校体制瓦解后，并没有中断“末代华校”群体热爱华文与华校的情意结——每天面对着求职受阻、英语霸权、以及华文降为“第二语文”等，种种无奈与不公平的现实环境，他们身心所承受的煎熬与创伤，导致一代人患上了“末代华校症候群”。本论文首先通过回顾新加坡华文教育发展的脉络，试析“末代华校”的形成。再来，因“末代华校”群体缺乏学术讨论，本论文必须借助新加坡报章（2003至2013年）、网络舆论与文学作品对于“末代华校”群体的讨论与再现，窥探他们在“末代”中的境遇，与近期所关心与期待的课题，并尝试勾勒出时代（“末代”至今）、华文教育与群体之间的紧密关系。最后，再从“末代华校”群体的访问中，初步探索语文源流统一政策在实行与颁布时间上的出入、试图整理出“末代华校”的历史分野（1975至1987年），以及获知他们亲身的经历，加以印证历史、集体记忆、认同与重申他们对新加坡华文教育的牺牲付出。Socio-economic restructuring and changes in education policies during the 1980s, led to the dissolution of the Chinese schools system in Singapore, however, the enthusiasm and love from the “last Chinese-educated generation” did not end here. The daily frustrations and helplessness and trauma from being hampered while seeking for jobs and economic survival, the tyranny of English hegemony, as well as the lowering of Chinese language status to being second language; has led to the development of the “last Chinese-educated generation complex”. This thesis will first attempt to analyze the formation of the “last Chinese-educated generation” through a review of the development of Chinese Language education in Singapore through time. Due to the lack of academic discussions about the “last Chinese-educated generation”, this thesis needs to seek first-hand information from Singapore’s newspapers (from 2003 to 2013), dialogue from netizens and literary works to formulate further discussions. This aims to re-look into the current concerns of the generation and reconstruct their close and dedicate relationship with the era (government) and Chinese language education. Then, through interviewing the “last Chinese-educated generation”, this thesis also attempts to re-evaluate the actual implementation time and announcement time of the “language streams unification policy” and sort out the historical time frame (1975 to 1987). Finally, to learn of their personal experiences and collective memory, and by relating it to historical events, this thesis hopes to reinstate their contributions and sacrifices made to Singapore’s Chinese Education.